E-174 Silk vista baby for the treatment of complex posterior inferior cerebellar artery aneurysms. (23rd July 2022) - Hanel, R; Benalia, V; Cortez, G; Brasiliense, L; Starke, R; Killer-Oberpfalzer, M; Lopes, D; Kan, P; Nogueira, R; Johnson, J; Pereira, V; Kilburg, C; et al.
Abstract : Introduction: Treatment of aneurysms in small-caliber vessels using flow diverters remains challenging. A narrow luminal diameter and vessel tortuosity are some of the encountered constraints when navigating 21 and 27 microcatheters, necessary to deliver conventional devices. The Silk Vista Baby (SVB, Balt) flow diversion device was designed for distal lesions, and to be delivered via a 0.017' microcatheter with ease-of-use in smaller diameter vessels. We analyzed the outcomes of SVB device on the treatment of truly PICA aneurysms in a multicentric retrospective cohort. Methods: Retrospectively collected data from 9 centers, including the United States, Canada, and Austria were reviewed to identify patients with true posterior communicating artery (PICA) aneurysms treated with the SVB Flow Diverter between January 2019 and June 2021. Inclusion criteria were aneurysms that originated from the posterior communicating artery (PICA) itself, primarily treated with Silk Vista Baby flow diverter; and at least one imaging control performed after the procedure. Patients were excluded if the aneurysm originated from the vertebra-basilar junction of the vertebral artery or the SVB was not used in the procedure. Primary outcomes of interest included target aneurysm occlusion according to Raymond-Roy classification and safety events, modified Rankin Scale (mRS) at discharge and 90-days, and postoperative complications. Mortality rates were based on the last follow-up. Categorical variables are reported as n (%), and continuous variables as mean± SD or median (IQR). Results: Fourteen patients harboring fifteen true PICA aneurysms were treated between January 2019 and June 2021. Nine were female (n=9; 64.2%), and mean age was 51 ± 14.9 years. Most were previously ruptured aneurysms, initially treated with a different endovascular technique. Six aneurysms were on the Telovelotonsilar segment (n=6; 40%). Mean neck size was 3mm (SD 1.35, range 2.5–5mm), whereas the mean PICA diameter was 1.6mm (SD 0.26, range 1.5–1.7mm). Mean length of follow-up was 6 months (SD 8.28, range 4.5–16). Complete occlusion, measured as Raymond-Roy class I was achieved in all cases. mRS at discharge and 90-days follow-up were similar, with 12 of 14 (85.7%) patients presenting a favorable outcome (mRS 0 or 1). Treatment-related adverse events included one case of transient hypoesthesia. Two additional events were reported but adjudicated as unrelated to the procedure. One patient with subarachnoid hemorrhage ([SAH], WFNS grade V) had a neurological decline after developing an external ventricular drainage-tract hematoma. The second patient presented with SAH due to a ruptured dissecting aneurysm. On imaging control, a fish-mouth narrowing of the device was identified, caused by a PICA vasospasm. A PICA-PCIA bypass was attempted as a rescue procedure, however, the surgery was not successful. Conclusion: PICA aneurysms beyond the origin are uncommon pathology, and the historical treatment for this lesion was either microsurgery, coiling, or stent-assisted coiling, but these treatment courses remain riddled with high rates of complications. The Silk Vista Baby flow diverter device presents as a suitable alternative as it can be delivered by a smaller and more maneuverable catheter, reducing the risks of complications and allowing the treatment of more distal and reduced caliber vessels. Disclosures: R. Hanel: 1; C; Unrestricted research grant from NIH, Interline Endowment, Microvention, Stryker, CNX. 2; C; Medtronic, Stryker, Cerenovous, Microvention, Balt, Phenox, Rapid Medical, and Q'Apel. 4; C; InNeuroCo, Cerebrotech, eLum, Endostream, Three Rivers Medical Inc, Scientia, RisT, BlinkTBI, and Corindus. V. Benalia: None. G. Cortez: None. L. Brasiliense: None. R. Starke: 1; C; NREF, Joe Niekro Foundation, Brain Aneurysm Foundation, Bee Foundation, and by National Institute of Health (R01NS111119–01A1) and (UL1TR002736, KL2TR002737) through the Miami Clinical and Translation. M. Killer-Oberpfalzer: 1; C; MicroVention Terumo. D. Lopes: 1; C; Medtronic and Stryker, being the national PI of the ADVANCE trial, receiving research grants and being part of their Advisory Board. P. Kan: 2; C; Stryker Neurovascular, Medtronic, and Cerenovus. R. Nogueira: 2; C; Anaconda, Biogen, Cerenovus, Genentech, Imperative Care, Medtronic, Phenox, Prolong Pharmaceuticals, and Stryker Neurovascular. 4; C; Astrocyte, Brainomix, Cerebrotech, Ceretrieve, Corindus Vascular Robotics, Vesalio, Viz-AI, and Perfuze. J. Johnson: None. V. Pereira: 1; C; Philips. 2; C; Stryker, Penumbra, and Balt, and as a consultant for Medtronic and Neurovasc. C. Kilburg: 2; C; Medtronic and Cerenovus. S. Khalili: None.